Developing biochemical teaching material based on research results of amino acid compound identification of seaweed (Dictyota patens) in the Segara beach Sanur - Eti Meirina Brahmana; I A Raka Astitiasih (University of Muhammadiyah Malang, 2017)
This study aims to identify the content of amino acids in seaweed (Dictyota patens) in Segara Sanur Beach which then developing teaching materials based on the results obtained. The method used to test the amino acids was HPLC, meanwhile the data collection has been done by employing questionnaires. The normality test was measured by using normality test, besides the homogeneity test and Paired Sample Test were also used to analyze the homogeneity and significant difference of the data gained. The development of teaching materials has been conducted through several stages namely: needs analysis, design of teaching materials, development of teaching materials, validation of teaching materials by experts, and experiments of teaching materials. The amino acid contents were done by using HPLC. The amino acids contained (% w/w) in the seaweed are aspartic acid (0.36), glutamate acid (0.57), serine (0.20), histidine (0.06), glycine (0.25), threonine (0.17), arginine (0.59), alanine (0.08), tyrosine (0.02), methionine (0.12), valine (0.22), phenylalanine (0.14), Isoleucine (0.16), leucine (0.33) and lysine (0.93). While in the development of teaching materials there is an increase in student learning outcomes by 0.28 with good criteria and there is a significant difference in students learning outcomes between the experimental class and control. Student response is 82.07% which means very strong toward the use of teaching materials.